Fabrication of LaFeO3 and rGO-LaFeO3 microspheres based gas sensors for detection of NO2 and CO. Issue 3 (7th January 2020) - Sharma, Neeru; Kushwaha, Himmat Singh; Sharma, S. K.; Sachdev, K.
Abstract : In the present report, gas sensing devices based on LaFeO3 and rGO-LaFeO3 were fabricated by a photolithography technique. Abstract : In the present report, gas sensing devices based on LaFeO3 and rGO-LaFeO3 were fabricated by a photolithography technique. The X-ray diffraction, Raman spectra and FT-IR results confirm the formation of a perovskite phase and composite. XPS and TEM give the chemical compositions for both products. The higher roughness, greater surface area (62.1 m 2 g −1 ), larger pore size (16.4 nm) and lower band gap (1.94 eV) of rGO-LaFeO3 make it a suitable candidate to obtain high sensitivity. The gas sensing performance of the devices was investigated for various concentrations of NO2 and CO gases at temperatures of 200 and 250 °C. It was observed that the rGO-LaFeO3 based device exhibited a high relative response (183.4%) for a 3 ppm concentration of NO2 at a 250 °C operating temperature. This higher response is attributed to the large surface area, greater surface roughness, and numerous active sites of rGO-LaFeO3 . The gas sensing properties investigated show that rGO-LaFeO3 is an excellent candidate for an NO2 sensor.